USE CASE - METHOD PROFESSIONAL DISCIPLINES FUTURE ECONOMISTS - Goncharova, O.M.; Cheporova Г. Є. (Journal of Information Technologies in Education (ITE), 2010)
The article is considered the features analysis of Case Study method of students teaching applicating information-communications technologies. Author’s experience of Case Study method application in the educational process is considered on economic specialities.